The Economic Cost of General Strikes in Nepal - Shrestha, Min Bahadur; Chaudhary, Shashi Kant (NRB Economic Review, 2014)
This paper reviews the key aspects of general strikes and analyses the economic cost of such strikes in Nepal. Data analysis shows that average direct cost of general strikes stood at NRs. 1.8 billion per strike day and NRs. 27 billion per year at current prices during 2008-2013. The lost output per year accounted for 1.4 percent of the annual gross output. The total accumulated output loss due to general strikes in the five-year period amounted to NRs. 117 billion. With such losses, general strikes decelerated annual GDP growth rates in a range between 0.6 percentage point and 2.2 percentage points during the study period. The impact of general strikes was quick and significant on inflation and tourist arrival rates. The monthly inflation rate jumped to over 9 percent as a result of two-day general strike while the strike called for three or more days led to an inflation of more than 10 percent. Similarly, tourist arrival declined over a lag. However, gross fixed capital formation and foreign direct investment appeared to be less affected by general strikes, which might be due mainly to their bottomed out levels.